The Influence of Dipole Moments Induced by Organic Molecules and Domain Structures on the Properties of CH3NH3PbI3 Perovskite. Issue 7 (25th April 2019) - Geng, Wei; Hu, Qi; Tong, Chuan‐Jia; Tang, Zhen‐Kun; Liu, Li‐Min
Abstract: Methylammonium lead iodide perovskite, CH3 NH3 PbI3, has attracted particular attention due to its fast increase in efficiency for solid‐state solar cells application. However, little is known about the influence of dipole moments of organic molecules on the electronic structures. In this study, first principles calculations are carried out to investigate the stability and electronic property of series structures with the different distributions of organic molecules and vacancy defects. The calculated results suggest that the configurations with the opposite dipole moments of MA + toward the PbI2 layers can greatly enhance the charge separation, which is caused by the local electric fields of dipole MA + ions. The direction and interval of localized charge are greatly dependent on the distribution of the MA + ions. Furthermore, the configurations with the opposite dipole of the MA + ions facing the PbI2 can be stabilized by vacancy defects. Abstract : CH3 NH3 PbI3 with the configurations of opposite dipole moments (MA + ) toward the PbI2 layers shows dramatic charge separations. Furthermore, the configurations with the opposite dipole of the MA + ions facing the PbI2 can be stabilized by vacancy defects.